In vitro selection of salinity tolerant variants from triploid bermudagrass (Cynodon transvaalensis x C. dactylon) and their physiological responses to salt and drought stress - Lu, Shaoyun; Peng, Xinxiang; Guo, Zhenfei; Zhang, Gengyun; Wang, Zhongcheng; Wang, Congying; Pang, Chaoshu; Fan, Zhen; Wang, Jihua (Plant cell reports, 2007)
A protocol was established for in vitro selection of salinity tolerant somaclonal variations from suspension cultured calli of triploid bermudagrass cv. TifEagle. To induce somaclonal variations the calli were subcultured for 18 months and were then subject to three-round selections for salt-tolerant calli by placing on solid medium containing 0.3 M NaCl for 10 days followed by a recovery for 2 weeks. The surviving calli were regenerated on regeneration medium containing 0.1 M NaCl. Three somaclonal variant lines (2, 71, and 77) were obtained and analyzed. The selected somaclonal lines showed higher relative growth and less injury than TifEagle under salt stress, indicating that they increased salt tolerance. In addition, they had higher relative water content and lower electrolyte leakage than TifEagle after withholding irrigation, indicating that they also increased drought tolerance. The three somaclonal variant lines had higher proline content than TifEagle under normal growth condition. The line 71 had a higher K⁺/Na⁺ ratio, whereas the lines 2 and 77 had higher CAT activity under control and salt stress conditions, indicating that different mechanisms for salt tolerance might exist in these three lines.